Couple found slain : after a family murder - Brottman, Mikita, 1966- (Henry Holt and Company, 2021)
"The story of Brian Bechtold, who killed his parents in 1992 at the age of twenty-two. Critically acclaimed author and psychoanalyst Mikita Brottman offers literary true crime writing at its best, taking us into the life of a murderer after his conviction-when most stories end but the defendant's life goes on"--